Segmentation and Targeting Analysis of Food Delivery Apps - Nico Pundarika; Ryco Syaputra; Willy Arafah (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study examines the segmentation and targeting strategies employed by food delivery app providers in Jakarta. It aims to identify the key factors influencing consumers' intentions to continue using these services across different market segments. A cluster analysis modeling approach is applied to group consumers based on specific characteristics. The findings provide valuable insights for marketers to design strategies that better align with the unique needs of consumers, considering both demographic and psychological factors. This enables marketers to adopt a more targeted approach in effectively addressing the preferences of each consumer segment. Additionally, the study highlights the importance of understanding the dynamics of the evolving demand within Indonesia's food delivery service sector. Ultimately, the research not only supports app providers in enhancing customer satisfaction but also fosters stronger loyalty towards their services. By leveraging a data-driven approach and more precise segmentation, food delivery app providers can refine their marketing strategies to engage consumers in a more relevant and sustainable manner.